Evaluation of Early and Late Harvested Potatoes for Yield, Quality and Storability - Das, Bimal; Sarkar, K. K.; Priya, Bhanu; Dudhane, A. S.; Pradhan, A. M.; Das, Aparajita (International Journal of Bio-resource and Stress Management, 2014)
Potato is an important food crop which is also valued in processing industries. Present experiment was undertaken to evaluate yield performance and storagability on 22 genotypes of potato along with quality parameters related to processing as well as cuisine purpose. The experiment was conducted in the field and laboratory of Dept. of Plant breeding, BCKV in 2011-12. In the study some of characters were measured such as dry matter, tuber shape and depth of eyes, chips color and quality, cooking type, texture firmness, flavor, starch and total sugar content. Genotypes G-4, Kufri Khyati, K. Chipsona-3 and PH-3 were found to be promising for their yield. Kufri Chipsona-3 and K-22 was found to be superior for processing purposes as these were associated with a number of desirable quality parameters like high dry matter content and starch content, low total sugar content and less blackening effect on cooked potato after cooling with persistence of good chip colour for a long period. For cuisine purposes K. Sadabahar and K. Jyoti was found to be most promising as they had tubers of good shape and shallow depth eyes, acceptable flesh colour and highly acceptable cooked potatoes. The varieties like K. Khyati, K. Pukhraj, K. Ashoka, PH-4 can be considered to increase flavor of cooked potatoes.